SLAMseq reveals potential transfer of RNA from liver to kidney in the mouse - Hunter, Robert W.; Sun, Jialin; Palmer, Trecia; Czopek, Alicja; Nespoux, Josselin; Bailey, Matthew A.; Dhaun, Neeraj; Buck, Amy H.; Dear, James W. (Nature communications, 2025)
Extracellular RNA (exRNA) mediates intercellular communication in lower animals; whether it serves a signalling function in mammals is uncertain. Reductionist experiments, in which a single RNA is over-expressed or tagged, have shown RNA transfer between tissues but may not be relevant to normal physiology. Here, we seek to determine the scale of RNA transfer between liver and kidney using metabolic RNA labelling in mice. We use 4-thiouracil to label RNA in hepatocytes and then detect labelled RNA in the kidney using SLAMseq: SH-Linked Alkylation for Metabolic RNA sequencing. We show that in the kidney, 5% of mRNA transcripts are labelled in health, increasing to 34% after acute hepatocellular injury. In the kidney, we do not detect labelled small RNA, but do find higher levels of the liver-enriched miRNA, miR-122 after liver injury. Our results show potential transfer of RNA from liver to kidney: a phenomenon that is augmented by liver injury. There were important limitations: we could not confidently identify transferred RNA transcripts at the single-gene level and we did not assess the physiological consequences of any RNA transfer. Hunter et al. use RNA labelling to investigate RNA transfer between organs in mice. They show that RNA potentially moves en masse from liver to kidney and that this movement is augmented in acute liver injury, although the physiological relevance of the phenomenon is not yet known.